Correspondence of Meningioma Orbital Grading and Clinicopathological Features among Indonesian Patients - Janah, Raudatul; Rujito, Lantip; Wahyono, Daniel Joko (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Orbital meningiomas can cause visual disturbances, protrusion of the eyes, double vision, and optic nerve abnormalities that significantly decrease vision and eventually lead to blindness. To the best of our knowledge, data on the incidence and pathogenesis of orbital meningioma in Indonesia are non-existent. AIM: This study aimed to analyze the clinicopathological relationship with orbital meningioma grading. METHODS: It is a cross-sectional observational analysis on 44 orbital meningioma patients in Dr. Hasan Sadikin General Hospital and the National Eye Center, Cicendo Eye Hospital in 2017–2020. Chi-square analysis and logistic regression with statistical significance (p < 0.05) were engaged in the method. RESULTS: Orbital meningioma mostly occurred in women aged 30–44 years. Meningioma Grade I was dominated by meningothelial meningioma found in 14 (31.8%) patients, Grade II was atypical meningioma in 9 (20.9%) patients, and Grade III was anaplastic meningioma in 3 patients (6.8%). Clinical symptoms in the form of papillary atrophy (p = 0.046), visual acuity (p = 0.026), proptosis (p = 0.029), and hyperostosis (p = 0.024) were statistically significant and there was a significant difference between Grade I, Grade II, and Grade III using the Chi-square test. Logistic regression results showed that hyperostosis is significantly related to grading the orbital meningioma (p = 0.044) with an odds ratio of 0.206 (IK95% 0.04–0.955). CONCLUSION: Hyperostosis increases the grading of the orbital meningioma because it is related to the invasion of the tumor into the orbital bone and is a neoplastic process. The presence of hyperostosis which is more common in Grade III meningiomas can be used as one of the most important predictors of meningioma recurrence postoperatively. Nonetheless, our data add to the existing literature the potential points of anti-invasive adjuvant therapy attacks.